Sifat Mekanik Gigi Tiruan Akrilik dengan Penguat Serat Gelas - Zuriah Sitorus; Awan Maghfirah; Yoshephin Romania; Syahrul Humaidi (Department of Physics, Sebelas Maret University, 2017)
The research is aimed to investigate the possibility of acrylic-reinforced glass fibre as a denture. Short glass fibre was made by variation of 4mm, 6 mm and 8mm. The results showed a good adhesion between glass fibre and acrylic resin with an optimum composition of the denture (acrylic: oil : glass fibre = 10 gr : 4.5 mL : 0.13 gr) was achieved. The density test was conducted by using Archimedes’ method, whereas compressive strength and tensile strength by using Universal Testing Machine (UTM). The results showed that glass fibre can be used to enhance the mechanical properties of acrylic resin. The optimum composition was achieved when 6 mm fibre had been added-in with a density of 1.2256 gr/cm3. A compressive strength of 76.623 MPa and a tensile strength of 71.207 MPa were recorded, these values can be applied as a denture.